Recognition of Robert E. Peary, the Arctic explorer . Report [to the House of Representatives] [to accompany S. 6104] - United States. Congress. House. Committee on Naval Affairs; United States. Congress. (61st, 3rd session : 1910-1911). House. ([Washington, D.C., 1911)
Mode of access: Internet.